A Critical Discourse Analysis of BBC News Online Coverage of the Gymnastics Ireland Racism Incident - Hayati, Dina Hilma; Umami, Habiba Al (English Literature Study Program, 2024)
Racism is a social phenomenon that continues to occur from the past until now. Advanced technological developments allow the spread of racism to become wider, one of which is through online newspapers. This research purposed to reveal racism through the use of inclusion and exclusion strategies by BBC News online media. This research also aims to reveal whether there is bias in this newspaper. This research used a critical discourse analysis approach. The data was taken from four articles of BBC News Online regarding the issue of the black girl published from September 24th until 28th, 2023. The data collected was data in the form of words, phrases, and sentences. Based on the inclusion and exclusion strategies proposed by Leeuwen (2008), this research found the two strategies were used by BBC News to represent the social actor. In the exclusion strategy, the strategy found was backgrounding while suppression was not found in this research. Then, this research found activations, assimilations, impersonalizations, functionalization, categorization, identification, passivation, and nomination while the rest strategies were not found in this research. From all of these findings, the most used strategy was activation. BBC News typically used this strategy to emphasize the action of Gymnastics Ireland in dealing with the racist issue. Moreover, BBC News was not neutral in reporting the news as Gymnastics Ireland was portrayed more negatively than the black girl.